Metabolic syndrome consequent to endocrine disorders - Popovic, Vera; Korbonits, Marta (Basel : Karger, 2018)
Hormonal dysfunction can have a major and often complex impact on all key components of the metabolic syndrome. This book comprises state-of-the-art reviews on the subject written by recognized experts in the field of endocrinology. Each chapter covers specific manifestations associated with the metabolic syndrome in classic endocrine diseases. Compelling questions are highlighted and future directions presented. The topics covered include hypopituitarism, adrenal insufficiency, acromegaly, glucocorticoid excess, androgen excess, hypogonadism, prolactin, and thyroid and parathyroid hormone abnormalities. This book is meant to inspire subsequent research related to metabolic complications in endocrine diseases, thus enabling early detection as well as prompt and appropriate management.
Keywords: SISTEMA ENDOCRINO -- ENFERMEDADES -- COMPLICACIONES; SÍNDROME METABÓLICO